(3HOGFY Gdfbhd aj JaUjd GdCUhds - (3eMeO Hf YHO GdSdGe GdeXaQjs; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3GdMeO ddg eDJj MbGFb GdMceI ade CLO cJCjjO GdeDjO CHbQGW aj aUhdg dcfg ChOYgG ehGVY JaJbQ Edi GdJChjd Ydi WQjb bjGSj s
(3BNQgG (B:s
(3jOd Ydi Cf eQVge bJGd, dCf GdUMI HGYJOGd GdeRGL hJfGSH GdgjFI, aYdi ebOGQ bdI JZjQgeG hcKQJg jchf VYa GdeQV hTOJg hSdGeJg hYWHg hGddg CYde s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JaSjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B37 s
Keywords: (3GdWHs